A Review of Circulating Tumor DNA in Hepatobiliary Malignancies - Mody, Kabir; Cleary, Sean P. (Frontiers in Oncology, 2018)
Circulating tumor DNA (ctDNA) released into circulation (blood) specifically from tumor cells (ctDNA) undergoing metabolic secretion, apoptosis or necrosis, carries tumor-specific genetic or epigenetic alterations. Technologies enabling clinical evaluation of ctDNA continue to advance rapidly and allow for assessment of patient specific tumoral genetic and epigenetic alterations. This holds great potential for earlier detection of disease, serial monitoring of tumor heterogeneity, identification of therapeutic targets, and evaluation of treatment response and mechanisms of resistance. Hepatobiliary malignancies are often diagnosed late, recur commonly, yield limited available tumor on biopsy, and harbor several genomic alterations with potential therapeutic impacts. Patients suffering from or at risk for these diseases thus stand to benefit immensely from this technology. Herein, we review the limited literature pertaining to the potential for ctDNA technologies in such patients. Patients with these cancers stand to benefit greatly from the application of ctDNA technologies, and concerted efforts at further investigation of such are ongoing and greatly needed.